Exosome secretion ameliorates lysosomal storage of cholesterol in Niemann-Pick type C disease - Strauss, Katrin; Goebel, Cornelia; Runz, Heiko; Möbius, Wiebke; Weiss, Sievert; Feussner, Ivo; Simons, Mikael; Schneider, Anja (The journal of biological chemistry, 2010)
Niemann-Pick type C1 disease is an autosomal-recessive lysosomal storage disorder. Loss of function of the npc1 gene leads to abnormal accumulation of free cholesterol and sphingolipids within the late endosomal and lysosomal compartments resulting in progressive neurodegeneration and dysmyelination. Here, we show that oligodendroglial cells secrete cholesterol by exosomes when challenged with cholesterol or U18666A, which induces late endosomal cholesterol accumulation. Up-regulation of exosomal cholesterol release was also observed after siRNA-mediated knockdown of NPC1 and in fibroblasts derived from NPC1 patients and could be reversed by expression of wild-type NPC1. We provide evidence that exosomal cholesterol secretion depends on the presence of flotillin. Our findings indicate that exosomal release of cholesterol may serve as a cellular mechanism to partially bypass the traffic block that results in the toxic lysosomal cholesterol accumulation in Niemann-Pick type C1 disease. Furthermore, we suggest that secretion of cholesterol by exosomes contributes to maintain cellular cholesterol homeostasis.